PENERAPAN PENCATATAN AKUNTANSI DAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK ETAP PADA UMKM DESA GEMBONGSARI KECAMATAN KALIPURO KABUPATEN BANYUWANGI - Deddy Kurniawansyah (UNEJ e-Proceeding)
This study aimed to: reveal the perception of SMEs about accounting and financial reporting process; describes the application of SAK ETAP on SMEs; reveal obstacles in the implementation of SAK ETAP on SMEs; prepare and develop guidelines based SAK ETAP accounting process for SMEs. This study used a qualitative approach. The population was MSMEs in the village Gembongsari. This study sample of 30 SMEs. Data collection techniques used were interviews, questionnaires and Forum Group Discussion. The results of indicate that SMEs do not require accounting information and stated that it is difficult to perform the accounting records with any limitations. Moreover, the need in the organization of accounting records is considered a waste of time and cost. Respondents recognized the importance of accounting records and preparation of financial statements in support of the sustainability of the company, but have not applied in accordance with SAK ETAP due to various constraints. SMEs in the village Gembongsari yet to implement appropriate accounting standards and has not been used optimally accounting information.